Evaluation of the Efficiency of Enterprises by the Method of Analysis of Functioning Environment - SAKHNO, Andrii; HRYVKIVSKA, Oksana; SALKOVA, Iryna; KUCHER, Lesіa (Journal of Environmental Management and Tourism; Vol 10 No 3 (2019): JEMT Volume X Issue 3(35) Summer 2019, 2019)
The purpose of the research is to assess the efficiency of enterprises by the means of analysis of the functioning environment, which made it possible to identify reserves for improving the results of their economic activity. For the first time, it was proposed to use the positioning (relocation) technique of enterprise positions, although previously the method of analysis of the functioning environment was used to determine the technical inefficiency of business entities. Based on the calculated line of technical efficiency on the actual results of the enterprises, a new line of technical efficiency was constructed by moving their positions to improve the income (revenue) from sales of products and labor costs of hired workers and capital (fixed assets) in the context of maximizing profits in the environment functioning of economic entities. It is proved that improvement of the position of an enterprise allows reducing expenses not only on capital, but also on wages of hired workers. Despite the ability to reduce capital expenditures and thus increase the cost of wage labor, almost all enterprises prefer saving capital over the possibility of investing in wage earners. The results of the study can be used by managers in planning the ways to achieve profit in the context of the sustainable development strategy of the enterprise.